(untitled) (Czech Journal of International Relations, 1992)
The Future of the Arab Nation - Challenges and Options. Zpracoval kolektiv autorů Centra studií o arabské jednotě pod vedením Khaira el-Dina Haseeba, Centre for Arab Unity Studies and Routledge, London-New York 1991, 520 stran.